The diversity of water markets: Prospects and perils for the SDG agenda. (23rd July 2019) - O'Donnell, Erin L.; Garrick, Dustin E.
Abstract: Water markets are used in a wide variety of contexts to (a) increase access to water, and (b) increase water use efficiency by reallocating water to uses with a higher economic value. The global prevalence of water markets may help or hinder achievement of Sustainable Development Goal 6, making it essential to understand their role in water management. However, an overarching understanding of what water markets are and how they work across different regulatory and geographic contexts is surprisingly elusive. The literature separates water markets based on their formality and the nature of the goods and services being sold (typically either domestic water or agricultural), but growing water scarcity and increasing urban water demands means that agricultural and urban water use can no longer be considered separately. This review brings together two disparate strands of literature on water markets: (a) markets as a tool for re‐allocation between agricultural uses (including both water rights and irrigation services), and (b) urban water markets to expand access to safe water supplies. Based on a review of 148 studies of water markets, this article explores the similarities and differences between urban and agricultural markets across the spectrum of regulatory formality to identify key findings in water market operation and outcomes, including critiques of market function. Bringing together the work on urban and agricultural water markets highlights important lessons on the role water markets can play in achieving SDG 6. This article is categorized under: Human Water > Value of Water Engineering Water > Sustainable Engineering of Water Abstract : Overcoming balkanization in water market research to explore the role of markets in achieving SDG 6.